Capital Markets Union: Deepening the Single Market Makes Sense, but Don't Expect too Much - Andreas Bley; Jan Philip Weber (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
The Capital Markets Union (CMU) is a flagship project of the European Commission that promotes a deepening of the financial markets. It aims at opening up new sources of funding for SMEs, as well as improving the matching between savers and borrowers. Additionally, CMU is supposed to increase the absorption capacity for asymmetric country-specific shocks. Some even see the CMU as a substitute for a fiscal union. However, it is questionable whether deeper financial market integration will succeed and materialize in a political and economic environment filled with severe uncertainties. – – Die Kapitalmarktunion (KMU) ist das Leuchtturmprojekt der Europäischen Kommission. Ziel der KMU ist eine tiefere Integration der nationalen Finanzmärkte in Europa, die unter anderem mit einer besseren Finanzierungssituation für mittelständische Unternehmen als auch einer effizienteren Interaktion von Sparern und Investoren einherginge. Darüber hinaus soll eine tiefere Integration der Finanzmärkte die Widerstandsfähigkeit gegen sogenannte ökonomische Schocks im Währungsraum erhöhen. In diesem Zusammenhang wird die KMU auch als ein Substitut für eine Fiskalunion gesehen. Angesichts der politischen und ökonomischen Unsicherheiten in Europa ist eine wesentlich tiefere Integration der Finanzmärkte zu dem gegenwärtigen Zeitpunkt allerdings sehr fraglich.
Keywords: E44; F36; G18; G28; 330; Financial markets; Capital Market Union; European Integration; risk absorption